Structural vibration characteristics of the historical building in a nearby blasting test - Ren, Yunsen; Xi, Shujuan; Yang, Yuhang; Wan, Tao; Wang, Haiyan; Zhao, Kai (Frontiers in Earth Science, 2024)
The tunnel construction by the drill-and-blast method can have a significant impact on the adjacent buildings, especially the historical buildings with poor structural performances. Based on a special explosive case of Nanjing Metro Line 4, an in-situ blasting test for vibration safety evaluation on the Nanjing Drum Tower was carried out. According to the site geological investigation, the location of the blasting test was selected near the planned tunnel. 6 blasting was carried out in terms of sing-hole blasting and millisecond-delay blasting. The attenuation of the ground vibration and the structural vibration responses of the historical Drum Tower were analyzed. The test results also showed that the Nanjing Drum Tower was not damaged by this blasting test. For single-hole blasting tests, the peak particle velocity increased with the increasing of the explosive charge, but decreased remarkably when using the millisecond-delay blasting technology. The horizontal and vertical ground vibration attenuation patterns were consistent, which can be described by the Sadowski formula. The ground vibration response was dominated by the horizontal vibration, and the velocity amplification factor in the case of the single-hole test with a charge quantity of 400 g reached 2.4, which was observed the most remarkable amplification effect.